Cegah Diare Melalui Tutorial Cuci Tangan Pakai Sabun Pada Siswa Sekolah Dasar di Kota Pekanbaru - Hetty Ismainar; Syafira Nurullita; Khaeratunnisa Fiyanmi; Mishbahuddin Mishbahuddin (STIKes Hang Tuah Pekanbaru, 2021)
Diarrhea is still a global disease that is often experienced by children, especially in developing countries. Based on the 2019 Basic Health Research data, diarrhea is the second leading cause of child mortality. It is necessary to prevent the incidence of diarrhea from an early stage. It trains clean and healthy living behavior through Hand Washing with Soap for students. Â Providing health education with the Hand Washing with Soap practice. The location is SD 192, Binawidya Village, Pekanbaru. The media used are videos and leaflets. The assessment indicators use a seven-step CTPS checklist before and after the provision of education. There were 11 students who participated in this activity accompanied by the teacher. The average CTPS practice pre-test score was 32.5% doing it correctly and 67.5% doing it incorrectly. After students were given education about the practice, it was seen that the results of the practice increased. On average, 88.3% have practiced CTPS correctly and only 11.7% have not done it correctly. There is an increase in students' CTPS practice scores by 55.8%. This practice of health educational activity is considered to be able to improve students' understanding of the practice of washing hands with seven steps correctly. ABSTRAK Diare masih merupakan penyakit global yang sering dialami anak terutama dinegara berkembang. Data Riset Kesehatan Dasar tahun 2018, prevalensi diare anak usia 5-14 tahun adalah 7% (182.338 kasus). Perlu upaya pencegahan insiden diare sejak dini. Melatih perilaku hidup bersih dan sehat melalui Cuci Tangan Pakai Sabun (CTPS) pada siswa Sekolah Dasar.Pemberian edukasi kesehatan dengan metode tutorial praktik CTPS. Lokasi di SD 192 Kelurahan Binawidya, Pekanbaru. Media yang digunakan pemutaran video praktik CTPS dan leaflet. Indikator penilaian menggunakan daftar tilik tujuh langkah CTPS sebelum dan sesudah pemberian edukasi. Ada 11 orang siswa yang mengikuti kegiatan ini dengan didampingi oleh wali kelas. Nilai pre-test praktik CTPS rerata 32,5% melakukan dengan benar dan 67,5% tidak melakukan dengan benar. Setelah siswa diberikan edukasi tentang praktik CTPS terlihat peningkatan hasil praktik tersebut. Rerata 88,3% telah melakukan praktik CTPS dengan benar dan hanya 11,7% saja yang belum melakukan dengan benar. Adanya peningkatan score praktik CTPS siswa sebanyak 55,8%. Kegiatan edukasi CTPS ini dinilai mampu meningkatkan pemahaman praktik siswa dalam mencuci tangan dengan tujuh langkah dengan benar.